Pemikiran Syekh Muhammad Nawawi al-Bantani al-Jawi tentang Pendidikan karakter dalam kitab Maraqi al-‘Ubudiyah ‘ala Matn Bidayah al-Hidayah - Aldianto Aldianto (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2019)
Character education in Indonesia has now become the concern of every group, this is due to the many deteriorating characters that occur in Indonesian society, such as corruption, law, theft and so on. Indonesia is not a country that lacks character education figures. In the 19th century, many Indonesians became big and influential scholars in the cities of Mecca and Medina, one of which was Sheikh Muhammad Nawawi al-Bantani al-Jawi. He has hundreds of students, and wrote 155 works in the form of bald Arabic (yellow book) which until now are scattered throughout Indonesia. This study aims to determine the concept, type and relevance of character education according to Sheikh Muhammad Nawawi al-Bantani in the Maraqi al-‘Ubudiyah book. The research method used is a qualitative descriptive approach with discourse analysis and data analysis in steps: first determining the theme, second arranging the problem, third formulating the problem according to the theme, fourth collecting data, and fifth concluding. The concept of religious character education according to Sheikh Nawawi has two concepts, the first is to worship both morals and behavior. The religious characters contained in the book Maraqi al-‘Ubudiyah are: adab associating with God, the behavior of righteous people, santri behavior to teachers, adab children to parents, adab to friends, emotion, gratitude, humility, glorifying God's creatures, Character education according to Syekh Nawawi is still relevant if applied to education in Indonesia.